2016
DOI: 10.3389/fpsyg.2016.01072
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Burnout among Student Nurses? An Exploration of the ICWR-1 Model of Individual Psychological Resilience

Abstract: The nature of nursing work is demanding and can be stressful. Previous studies have shown a high rate of burnout among employed nurses. Recently, efforts have been made to understand the role of resilience in determining the psychological adjustment of employed nurses. A theoretical model of resilience was proposed recently that includes several constructs identified in the literature related to resilience and to psychological functioning. As nursing students are the future of the nursing workforce it is impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 49 publications
9
63
0
Order By: Relevance
“…However, self‐efficacy did not directly influence burnout (H3). This result was congruent with a previous study by Rees et al (). However, it was inconsistent with Bandura's () explanation that when people have a high rate of self‐efficacy, they may experience low rate of burnout.…”
Section: Discussionsupporting
confidence: 94%
“…However, self‐efficacy did not directly influence burnout (H3). This result was congruent with a previous study by Rees et al (). However, it was inconsistent with Bandura's () explanation that when people have a high rate of self‐efficacy, they may experience low rate of burnout.…”
Section: Discussionsupporting
confidence: 94%
“…CD‐RISC‐10 scores range from 0 to 40 (higher scores indicating elevated resilience). Multiple Australian studies with nurses and nursing students showed that the CD‐RISC‐10 had good psychometric properties (Craigie et al, ; Rees et al, ; Slatyer, Craigie, Heritage, Davis, & Rees, ).…”
Section: Methodsmentioning
confidence: 99%
“…With this knowledge, there is a need to explore facets of resilience, including the role that individual and workplace factors play in promoting or diminishing resilience. Numerous studies have examined the relationship between individual factors and psychological resilience in nurses (Gillespie, Chaboyer, Wallis, & Grimbeek, ; Hegney, Rees, Eley, Osseiran‐Moisson, & Francis, ; Rees et al, ). Gillespie et al () found competence, coping, control, self‐efficacy, and hope were all attributes associated with resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupational resilience is a construct that continues to receive much research attention due to its prospective mitigating influence on less‐desirable workplace outcomes, such as burnout and turnover (Lee et al, ; Rees et al, ). Resilience is commonly considered as an individual differences variable that modifies the way people respond to, and consequently bounce back from, risky or psychologically taxing scenarios (Fraser, Richman, & Galinsky, ).…”
Section: Introductionmentioning
confidence: 99%